Utility of an alternative method (to USEPA Method 1613) for analysis of priority persistent organic pollutants in soil from mixed industrial–suburban areas of Durban, South Africa. (23rd September 2022) - Rimayi, Cornelius; Madikizela, Lawrence M.
Abstract: This study evaluates the adequacy of a USEPA Method 1613 alternative analytical method for analysis of persistent organic pollutants (POPs) in soil from the immediate vicinity of industrialized areas in the eThekwini municipal area in South Africa. The objective of this study is in line with the Stockholm Convention Article 11 on research, development, and monitoring. Furthermore, it became imperative to find an alternative analytical procedure to USEPA Method 1613 that could cater to studies conducted in Africa where recent reviews have indicated that most African countries lack the technical and instrumental capacity for performing analysis of dioxin‐like compounds according to USEPA Method 1613, which entails the use of high‐resolution chromatography and high‐resolution mass spectrometry instrumentation. The study aimed to ascertain the utility of an alternative two‐dimensional gas chromatography‐time of flight mass spectrometry method for analysis of trace‐level priority POPs in soil, along with a fast single quadrupole gas chromatography‐mass spectrometry method. The analytical methods were applied to the analysis of POPs on soil samples from industrial areas with oil refineries and a pulp and paper manufacturing company, while other samples were collected near the electricity substations and a landfill site. Analytical results showed BDE 209 as the dominant contaminating polybrominated diphenyl ether (concentration ranges from 0.006 to 5.71 ng g −1 ). Polybrominated biphenyls (PBBs) 9, 10, and 49 were the dominant PBBs detected in 78% of the sites tested, although their concentrations were below the limit of quantification (LOQ). Polychlorinated dibenzo‐ p ‐dioxins and furans and dioxin‐like polychlorinated biphenyls detected could not be quantified above their respective LOQs, indicating that the Durban area has low priority pollutant contamination levels compared to other regions around the world. The methods developed are a starting point that will inform considerations for routine evaluation and management of soil contamination, which plays a vital role in environmental management. Integr Environ Assess Manag 2023;19:749–762. © 2022 SETAC Key Points: With limits of quantification of dioxin‐like PCBs ranging from 2.12 to 7.83 pg g −1 and non‐octa‐PCD/Fs ranging from 10 to 41.67 pg g −1, the alternative GC × GC‐TOF method can be used to quantify significantly high concentrations of priority pollutants from the environment and other sample matrices. The alternative GC × GC‐TOF method can enable developing countries to comply with the Stockholm Convention articles,  develop sound local environmental management policies, and implement strong regulations of both local and international environmental laws. This study provides a framework for African countries to achieve and build local capacity and competence in dioxin‐like compound analysis, and shift from a reliance on developed countries.